Out of Pocket Payment and Affordability of Medication for Geriatric Patients in Tehran, Iran - Morvarid ZARIF-YEGANEH; Mona KARGAR; Arash RASHIDIAN; Aarefeh JAFARZADEH KOHNELOO; Kheirollah GHOLAMI (Tehran University of Medical Sciences, 2019)
Background: Considering the importance of high out-of-pocket (OOP) payment (OOPP), as a marker of health system performance, and affordability of medications in the elderly, this study was conducted to determine these issues. Methods: In this cross-sectional study, prescriptions of patients aged 65 yr or older from 5 university-affiliated pharmacies in Tehran, Iran were evaluated from Jan to Mar 2014. Prescriptions were selected from four insurance organizations. We used the prescriptions data regarding patients' demographics and the prescribers as well as the sales data for OOP. Affordability was calculated by considering the daily salary of an unskilled worker. Results: Totally, 1467 prescriptions were analyzed. Mean age of patients was 73.89(6.66) yr. Mean (SE) of reimbursable and OOPP of the prescriptions were 203820 (10831) and 230252 (10634) IRR (Iranian Rials) respectively (equivalent to 81.6 (4.33) and 92.17 (4.33) US$ respectively). Subspecialists imposed higher expenditures for patients and insurance organizations. Patients referred to the ophthalmologists paid less OOP. Nearly 50% of the total prescription costs was paid as OOP. The mean OOPP was averagely equal to 1.41(0.065) daily salary. These prescriptions were unaffordable for 36.2% of patients. Conclusion: The OOPP was higher than the insurance goal of 30% for outpatients in Iran. More than one-third of elderly patients could not afford their single prescription. Due to the health consequences of the unaffordability of medications, corrective actions are needed by the insurance organizations and the health system.